The Ambient Temperature Influence on the Modelling of Power Distribution Networks - Vrcelj, Nada S; Milošević, Dejan N; Šušnica, Nikola K; Stanojević, Vesna A (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
For long-term development planning of power distribution networks, it is necessary to have the modelling process adapted to the available data. More detailed models can give better insight into the current operating state of the power distribution network, as well as into the potential network capabilities. The impact of conductor resistance change due to ambient temperature variations in power distribution network modelling is analysed, especially the influence on power flow calculations and estimated power losses. This impact is analysed in the case of a part of the power distribution network EPS Distribucija d.o.o. Beograd, which includes the network areas Sopot and Grocka.